2014
DOI: 10.1017/s0007123414000428
|View full text |Cite
|
Sign up to set email alerts
|

The Political Conditioning of Subjective Economic Evaluations: The Role of Party Discourse

Abstract: 7Classic and revisionist perspectives on economic voting have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 64 publications
1
32
0
Order By: Relevance
“…The level of positive sentiment parties exhibit in their campaigns should also vary with objective measures of the state of the world. While parties will try to use the emotive content of their campaigns to get voters to see the world through a particular frame, the extent to which they can do this is constrained by economic reality (Parker-Stephen, 2013;Pardos-Prado and Sagarzazu, 2016). Campaign messages that are too positive when times are bad or too negative when times are good are likely to be ignored by voters as they deviate from their own personal experiences (Ansolabehere, 2006).…”
Section: Theorymentioning
confidence: 99%
“…The level of positive sentiment parties exhibit in their campaigns should also vary with objective measures of the state of the world. While parties will try to use the emotive content of their campaigns to get voters to see the world through a particular frame, the extent to which they can do this is constrained by economic reality (Parker-Stephen, 2013;Pardos-Prado and Sagarzazu, 2016). Campaign messages that are too positive when times are bad or too negative when times are good are likely to be ignored by voters as they deviate from their own personal experiences (Ansolabehere, 2006).…”
Section: Theorymentioning
confidence: 99%
“…To determine the latter, the categorical coding scheme developed by the Conflict and Mediation Event Observation (CAMEO) 32 Adams, Ezrow, and Somer-Topcu 2014;Adams, Ezrow, and Wlezien 2016. 33 Herzog and Benoit 2015;Martin and Vanberg 2008;Proksch and Slapin 2015;Pardos-Prado and Sagarzazu 2016;Schwarz, Traber, andBenoit 2017. 34 Grimmer 2013;Grimmer, Westwood, and Messing 2015;Sagarzazu and Klüver 2017.…”
Section: Machine Coded Event Datamentioning
confidence: 99%
“…4 See, e.g., Bakker et al 2015;Budge et al 2001. 5 See, e.g., Grimmer 2013;Grimmer, Westwood, and Messing 2015;Herzog and Benoit 2015;Pardos-Prado and Sagarzazu 2016;Proksch and Slapin 2015;Sagarzazu and Klüver 2017;Schwarz, Traber, and Benoit 2017. 6 Hoff, Raftery, and Handcock 2002;Hoff 2005. 7 That is, in a one-dimensional space, they are both placed to the left or the right of the zero point.…”
mentioning
confidence: 99%
“…The only exception was 2004, yet there are strong reasons to believe that the Madrid bombings heavily influenced the 2004 wave results. Second, research has found no relationship between economic competence and voting for the PSOE (Hamann, ), while at the same time finding a strong relationship between the PP and economic ownership (Pardos‐Prado and Sagarzazu, ). Third, socialist governments are associated with poor macroeconomic performance first during the democratic stabilization period of the 1980s and early 1990s and second during the postfinancial crisis in the late 2000s.…”
Section: Theorymentioning
confidence: 99%
“…As we mentioned above, these objectives are easier to meet if there is only one speaker (such as a speech). In either case, these two strategies have been linked together in the literature as we have found (not without disagreements) that issue attention by politicians is directly linked to the way people evaluate leaders and governments and can very well determine electoral outcomes (see, for instance, Petrocik, ; Ansolabehere and Iyengar, ; Williams, Seki, and Whitten, ; Pardos‐Prado and Sagarzazu, ). The strategic nature makes these debates that much more informative for analyzing the effects of political communication.…”
mentioning
confidence: 98%